The Trade Development Among OIC Countries: Exploring Challenges, Opportunities, and the Impact of the Covid-19 Pandemic - Bhatti, M. Ishaq; Ghouse, Ghulam (Muslim Business and Economics Review, 2023)
This paper investigates the factor determining the impact of trade development, challenges, and opportunities among various OIC countries. It studies the impact of socioeconomics, geo-political and cultural, factors using data between 2014 to 2022. The selected OIC countries from diverse regions, namely South and Southeast Asia, South America, Europe, Africa, and Central Asia. The study’s sample includes 50 countries out of a total of 57 OIC member nations. The paper employs a two-step GMM model to address endogeneity issues related to institutional variables. To account for the impact of the Covid-19 pandemic on trade, we have included a Covid-19 dummy variable in the model. Our results reveal that the Covid-19 dummy variable is significant in all models, indicating its significant impact on trade. Furthermore, most of the variables included in the study are found to be significant in all models. Overall, this study provides valuable insights into the factors that influence trade in OIC countries and the impact of the Covid-19 pandemic on trade.